Mechanistic insights into pincer-ligated palladium-catalyzed arylation of azoles with aryl Iodides: evidence of a Pd-II-Pd-IV-Pd-II pathway - Khake, Shrikant M.; Jagtap, Rahul A.; Dangat, Yuvraj B.; Gonnade, Rajesh G.; Vanka, Kumar; Punji, Benudhar (Organometallics, 2016)
Pincer-based (R2POCNR′2)PdCl complexes along with CuI cocatalyst catalyze the arylation of azoles with aryl iodides to give the 2-arylated azole products. Herein, we report an extensive mechanistic investigation for the direct arylation of azoles involving a well-defined and highly efficient (iPr2POCNEt2)PdCl (2a) catalyst, which emphasizes a rare PdII–PdIV–PdII redox catalytic pathway. Kinetic studies and deuterium labeling experiments indicate that the C–H bond cleavage on azoles occurs via two distinct routes in a reversible manner. Controlled reactivity of the catalyst 2a underlines the iodo derivative (iPr2POCNEt2)PdI (3a) to be the resting state of the catalyst. The intermediate species (iPr2POCNEt2)Pd-benzothiazolyl (4a) has been isolated and structurally characterized. A determination of reaction rates of compound 4a with electronically different aryl iodides has revealed the kinetic significance of the oxidative addition of the C(sp2)–X electrophile, aryl iodide, to complex 4a. Furthermore, the reactivity behavior of 4a suggests that the arylation of benzothiazole proceeds via an oxidative addition/reductive elimination pathway involving a (iPr2POCNEt2)PdIV(benzothiazolyl)(Ar)I species, which is strongly supported by DFT calculations.